A percepção do zumbido pode ser modulada pela resiliência, personalidade e/ou sintomas psiquiátricos? - Martins, Mariana Lopes (2018)
Tinnitus is the perception of sound in the absence of external sound stimulus, and is perceived in different ways. The presence of tinnitus may be associated with neuropsychiatric disorders and be influenced by personality traits. Resilience is one of the ways to seek improvement through the use of adaptive resources, and plays a key role in desensitizing the influence of tinnitus perception. Objective: To investigate the relation of resilience to the perception and annoyance of tinnitus, having as mediators, psychiatric symptoms and personality traits. Method: The instruments that were used for tinnitus data collection are the specific anamnesis for tinnitus, for collecting general symptom data; Tinnitus Handicap Inventory (THI) and Analog Visual Scale (EVA) for buzz nuisance data. In addition to acuphenometry, to obtain the sensation of frequency and intensity of tinnitus in each ear. To collect the psychological data, the Resilience Scale was used to obtain the three factors: Resolutions of Actions and Values; Independence and determination; Self-confidence and adaptability to situations; Big Five Inventory, (BFI) for collection of personality traits; and Adult Self-Report (ASR), to obtain data on psychiatric symptoms. Descriptive and inferential statistics were used through the t test, correlation, linear regression and multiple regression. Results: There was an association between tinnitus nuisance, personality (p <0.001 for neuroticism and openness to experience) and psychiatric symptoms (p = 0.013 for Anxiety and Depression, p = 0.011 for somatic complaints, p = 0.004 for internalisation of problems, p = 0.025 for critical items guided by the Diagnostic and Statistical Manual of Mental Disorders (DSM). It was also observed association with the items of anxiety and depression in the right ear (p = 0.03) and somatic complaints in the left ear (p = 0.002), but no personality relationship was observed with sound intensity (p> 0.05). In addition, resilience has been shown to mediate between general emotional health (psychiatric symptoms) and the annoyance of tinnitus. Thus, it has a minor effect on the characteristics of tinnitus. However, resilience can serve as an indicator for future development of tinnitus-related suffering. Conclusion: Psychiatric symptoms and personality traits influence the perception of tinnitus, but no interference of resilience was observed. Thus, it is interesting that more in-depth psychological evaluations are performed in the population with tinnitus, so that it is possible to perform the appropriate treatment for each individual.